Determinação do nível crítico de fósforo do solo com auxílio do P32 (nota prévia) - Mello, Francisco A.F. de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1970)
In this paper the author presents a preliminary study carried out in order to determinate the phosphorus critical level in soil using the CATE & NELSON'S (1965) sistem but evalúating the content of that nutrient be the LARSEN'S (1952) L value. It was found that the critical level sought is about 30-35 ppm of phosphorus.